Wilms Tumor in India: A Systematic Review - Srinivasan, Shyam; Ramanathan, Subramaniam; Prasad, Maya (South Asian Journal of Cancer, 2022)
Background Cure rates of childhood malignancies are inferior in India compared with upper-middle-income countries. There is paucity of quality data addressing outcome of childhood Wilms tumor (WT) from India. This systematic review was conducted to assess the disease trends, treatment strategies, and outcome indicators in WT across India.Materials and Methods We conducted a systematic search of MEDLINE, Google Scholar, and SCOPUS database, and additionally screened International Society of Pediatric Oncology conference abstracts. Data concerning WT or nephroblastoma published from India were extracted.Results A total of 17 studies containing 1,170 patients were included in this review. Ninety-four percent of the studies were published after the year 2010. Advanced stage (III and IV) disease was seen in 46% of included patients. In seven studies, patients underwent a pretreatment biopsy before commencement of therapy. A hybrid approach consisting of “surgery first” in a selected subset and “neo-adjuvant chemotherapy” in all others was the most common treatment strategy adopted in half of the studies. The overall survival ranged between 48 and 89%. Key prognostic factors influencing survival across studies included increased tumor volume, metastatic disease, and unfavorable histology. Nonrelapse mortality (2.7–8.5%) was noted to be high.Conclusion Substantial proportion of children with WT from India present with advanced stages of the disease. Despite several limitations, the current systematic review showed a modest survival among Indian children with WT. Adopting strategies through collaboration to ensure early access to expert care along with involvement of social support team to improve compliance may further improve survival of WT in India.
Keywords: Wilms tumor; India; survival; prognostic factors